Changing School Education Amidst COVID-19 Pandemic: Perspectives from Rajasthan - Agarwal, Tasha; Kaur, Deepinder; Arora, Jyoti (INDIAN EDUCATIONAL REVIEW, 2020)
The sudden emergence of the Covid-19 pandemic has created a crisis situation which, apart from health, has impacted the education sector the most. The online schooling system has created a new form of classroom supported by digital technology. This new classroom setup has changed the entire course of the teaching and learning process. Where the teachers are facing additional challenges of coping up with technology leading to increased workload, the issues of access and efficiency of technology remains a central problem for both students as well as teachers. Along with that, never before had the involvement of parents been so central in the daily learning experiences. This paper analysed how the new school education was perceived by different stakeholders in the Rajasthan state of India. Through surveys and interviews, the paper examined the paradigm shift from the physical classroom to the online classroom through the lens of teachers, students and parents.